Environmental parameters and growth of cage-cultured blood cockle Tegillarca granosa in Aceh, Indonesia - MAWARDI MAWARDI; TRI MUSTIKA SARJANI; MUHAMMAD KHALIL; ANITA RASUNA SARI SIREGAR (Society for Indonesian Biodiversity, 2026)
Abstract. Mawardi, Sarjani TM, Khalil M, Siregar ARS. 2026. Environmental parameters and growth of cage-cultured blood cockle Tegillarca granosa in Aceh, Indonesia. Biodiversitas 27 (3): d270307. https://doi.org/10.13057/biodiv/d270307. This study evaluated the growth performance of cage-cultured blood cockle Tegillarca granosa and the environmental parameters influencing it in two mangrove-fringing coastal waters in Aceh, Indonesia. A randomized block design was used with three stocking densities (20, 40, and 60 individuals per cage) at Pusong and Lhok Banie. Water quality variables—including temperature, salinity, pH, organic matter, and sediment characteristics—were measured throughout the culture period. Growth parameters (shell length, width, and weight) and environmental factors (sediment type, salinity, and plankton abundance) were monitored for six months. Data were analyzed using Specific Growth Rate (SGR), ANOVA, and Principal Component Analysis (PCA). Results showed that growth in length ranged from 3.07-8.00 mm, width from 2.48-5.45 mm, and weight from 2.63-5.60 g. The highest growth was recorded at Pusong (P1, 20 individuals/cage), while the lowest was at Lhok Banie (LB3, 60 individuals/cage). The SGR ranged from 0.18-0.30 g. PCA indicated that sediment composition dominated by clay and clayey loam, together with salinity of 24-28‰, had the strongest positive relationship with cockle growth. Overall, the findings demonstrate that T. granosa grows better in areas with higher salinity and organic-rich sediments, and that a stocking density of 20 individuals per cage yields the most favorable growth performance. These results provide baseline information for improving community-based blood cockle aquaculture and support the development of sustainable mangrove-associated coastal farming systems in Aceh.